2022
DOI: 10.35848/1347-4065/ac8d9e
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tracer diffusion analysis and observation of domain structure in quenched (Bi0.5Na0.5)TiO3ceramics

Abstract: Lead-free ferroelectric and piezoelectric ceramics, (Bi0.5Na0.5)TiO3 [BNT] ceramics were prepared by controlling the quenching rate (QR). The quenching effects mainly caused increase in lattice distortion 90-α and T d, contribution of electrical properties and ordered structural phase transitions. In this study, we analyzed oxygen tracer diffusion and examined domain structures for quenched BNT ceramics, and then we proposed a mechanism for the quenching effect. As a result, the diffusion coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In another study, Takagi et al analyzed oxygen tracer diffusion and examined the domain structures of the quenched BNT composition by controlling the quenching rate and compared with those of BNT with soft and hard dopants. 57) The report indicated that the diffusion coefficients, D, of 18 O tracer for the conventionally-fired and quenched samples were 2.5 × 10 -11 and 1.8 × 10 -11 cm 2 s −1 , respectively, and no significant differences were observed in the oxygen vacancies of quenched samples in hard and soft compositions as well. It was indicated, however, that the domain size of BNT in the quenched samples was about twice that of the unquenched BNT ceramics [Figs.…”
Section: Bnt-bkt-blt Systemmentioning
confidence: 96%
See 2 more Smart Citations
“…In another study, Takagi et al analyzed oxygen tracer diffusion and examined the domain structures of the quenched BNT composition by controlling the quenching rate and compared with those of BNT with soft and hard dopants. 57) The report indicated that the diffusion coefficients, D, of 18 O tracer for the conventionally-fired and quenched samples were 2.5 × 10 -11 and 1.8 × 10 -11 cm 2 s −1 , respectively, and no significant differences were observed in the oxygen vacancies of quenched samples in hard and soft compositions as well. It was indicated, however, that the domain size of BNT in the quenched samples was about twice that of the unquenched BNT ceramics [Figs.…”
Section: Bnt-bkt-blt Systemmentioning
confidence: 96%
“…This suggests that quenching of these ceramics increases domain size and decreases domain wall density, inducing lattice distortion that results in increased T d , thus affecting electromechanical properties. 57) In addition to the investigations on soft BNT-BKT-BT, Yesner et al have evaluated the effect of non-stoichiometric compositions 0.88Bi 0.50−x Na 0.50 TiO 3 -0.08Bi 0.50−x K 0.50 TiO 3 -0.04BaTiO 3 aiming to develop hard Pb-free piezoelectric materials. 32) Hard BNT-based piezoelectrics were developed by Bi-deficient or alkali-excess compositions and were found to have increased Q m .…”
Section: Bnt-bkt-blt Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Despite this, an oxygen tracer diffusion study of as-processed and quenched NBT did not reveal any significant variation in oxygen vacancy concentration due to the quenching. 38 Although quenching has been found to increase the stability range of the field-induced ferroelectric state in different compositions, their underlying mechanism is not well-established. 31 Studies on the influence of rapid cooling/quenching on A-site complex KBT are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth sodium titanate Bi 0.5 Na 0.5 TiO 3 (BNT) is a lead-free piezoelectric material that exhibits relatively good piezoelectric properties. [1][2][3][4][5][6][7][8][9] BNT has also been developed as a stable battery electrode and energy storage materials suitable for working over a wide temperature ranges. 10,11) Accordingly, the methods for synthesizing high-quality BNT samples have been developed.…”
Section: Introductionmentioning
confidence: 99%